SARANA-OLAHRAGA VERTIKAL JAKARTA - Tian Tian; Suwardana Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The Millennials, also known as Generation Y (Gen-Y) refer to a generation with people who were born in between 1981-1994, in which they have become dominant in the society and are in their productive phase. The millennials are certainly inevitable from the existence of automation resulting in an easier and faster way in doing various activities and fulfilling needs, moreover, many activities can be carried out simultaneously with the existence of this automation. This habit is increasingly becoming the lifestyle of these millennials in which they are heavily dependent on current and future technological advancements. For that matter, human beings are living things that have limits in terms of developing meanwhile, technologies currently are rapidly advancing. This means that these millennials will gradually lose their ability to keep track of the development of these technologies. Health is one of the keys for these millennials to be able to carry out activities and keep up with current technological developments. By creating a sports facility that functions as a means of recreation and health in the midst of the dense activities in Central Jakarta, precisely in Jl. H. Agus Salim, a design approach that focuses on providing space that can be used for sports and can be placed in the middle of the city, is given out to satisfy the necessity of having this kind of facility, in the hope of balancing the needs of these millennials for recreation in the middle of their crowded activities in the city. AbstrakGenerasi Millennial (Gen-Y) merupakan generasi yang lahir antara tahun 1981-1994, yang menjadi masyarakat dominan dan sedang dalam masa produktif mereka. Generasi millennial yang tidak terhindarkan dari otomatisasi, yang membuat segala kegiatan dan kebutuhan menjadi lebih mudah dan cepat, terlebih lagi banyak kegiatan yang dapat dilakukan secara bersamaan dengan adanya otomatisasi ini. Kebiasaan ini kian menjadi gaya hidup generasi millennial yang bahkan sangat bergantung kepada kemajuan teknologi yang ada sekarang dan yang akan datang. Selayaknya manusia sebagai makhluk hidup yang punya keterbatasan untuk berkembang yang bertolak belakang dengan teknologi sekarang yang terus meningkat, yang berarti generasi millennial ini sedikit demi sedikit akan kehilangan kemampuan mereka untuk mengikuti laju perkembangan teknologi tersebut. Kesehatan menjadi kunci generasi millennial untuk tetap dapat beraktivitas dan mengikuti perkembangan teknologi saat ini. Dengan menciptakan sebuah sarana olahraga yang berfungsi sebagai sarana rekreasi dan kesehatan dari padatnya aktivitas di daerah Jakarta Pusat, tepatnya pada Jl. H. Agus Salim, pendekatan desain yang memfokuskan kepada penyediaan ruang yang dapat digunakan untuk berolahraga yang dapat di tempatkan di tengah kota untuk menjawab keterjangkauan sarana olahraga ini, dengan harapan dapat menyeimbangkan kebutuhan generasi millennial akan sarana rekreasi dari padatnya aktivitas di tengah kota.